2017
DOI: 10.3324/haematol.2017.178442
|View full text |Cite
|
Sign up to set email alerts
|

A 29-gene and cytogenetic score for the prediction of resistance to induction treatment in acute myeloid leukemia

Abstract: Primary therapy resistance is a major problem in acute myeloid leukemia treatment. We set out to develop a powerful and robust predictor for therapy resistance for intensively treated adult patients. We used two large gene expression data sets (n=856) to develop a predictor of therapy resistance, which was validated in an independent cohort analyzed by RNA sequencing (n=250). In addition to gene expression markers, standard clinical and laboratory variables as well as the mutation status of 68 genes were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 36 publications
1
88
0
Order By: Relevance
“…2B. Many of the genes significantly differentially expressed at a false discovery rate (FDR) < 0.05 have previously been implicated in drug resistance across multiple cancers, including BAK1, PPP1R13L, and NFKBIE (19,(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B. Many of the genes significantly differentially expressed at a false discovery rate (FDR) < 0.05 have previously been implicated in drug resistance across multiple cancers, including BAK1, PPP1R13L, and NFKBIE (19,(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to cytogenetic and molecular factors, other risk factors for primary refractory disease include clinical variables such as older age and an antecedent hematological neoplasm (13)(14)(15). Recent studies have suggested that primary treatment failures might also be the result of AML clones harboring intrinsic properties of hematopoietic stem cells and quiescence, and gene expression signatures may be predictive of outcome (11,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…RNA-Seq data sets from AML patient samples were previously described including the informed consent and ethical issues [29][30][31]. Reads were mapped with STAR aligner version 2.7.2d using GRCh37 reference and annotation version 32 from GENCODE (www.gencodegenes.org).…”
Section: Aml Patients and Statisticsmentioning
confidence: 99%
“…Gene annotations were obtained from Ensembl (GRCh38.84/GRCm38.75). Analysis of RNA sequencing data followed standard recommendations (43). Statistical analysis was performed using the R 3.6.1 software package (R Core Team, 2019).…”
Section: Flow Cytometric Analysis Of Bh3 Proteins' Level Andmentioning
confidence: 99%